Review: Guerric of Saint-Quentin. Quaestiones de quolibet - Evans, Gillian (The journal of theological studies, 2003)
Guerric of Saint-Quentin. Quaestiones de quolibet † Walter H. Principe CSB. Editorial revision and preface by Jonathan Black Introduction by Jean-Pierre Torrell OP. Pp. xxxv+462 (Studies and Texts, 143) Toronto Pontifical Institute of Mediaeval Studies 2002 0 88844 143 6 $ 84.95